The Model of Psychological Service of Higher Educational Establishment - Gasyuk, Myroslava Bogdanovna (Psychological Prospects Journal, 2012)
The article presents a new approach to the activities and functions of psychological service of a higher educational establishment. Psychological service’s created model of higher educational establishment in Ukraine according to the requirements of modern psychology and time. The tasks of the psychological service of the future, the main directions, forms and methods of their implementation, as well as a system of psychological service in higher educational establishments are outlined.